Micropropagation of Elite Genotypes of Castanea Sativa (MILL.) - Aravanopoulos, Filippos A. (Phil); Tchatchoua, Dorothy T.; Barbas, Evangelos (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Sprouted buds of eight mature plus-trees of Castanea sativa were collected from two natural populations (Mt. Paiko and Mt. Hortiatis, Greece). Explants were cultured on Murashige and Skoog (MS) medium (three concentrations of macro and micro-elements) combined with three concentrations of BAP (6-Benzylaminopurine). Results were evaluated based on three multiplication traits: (a) number of shoots produced, (b) length of the longest shoot segments and (c) percentage of responsive explants. A high genotype-dependant variation for the number of shoots produced per explant was detected. MS medium at full salt strength and 0.2 mg l-1 BAP provided the best results based on the multiplication traits measured. Elite mature tree P-2 proved to be highly favourable for multiplication. Rooting was attempted on ½ MS medium at five different NAA concentrations. Successful rooting (56%) was obtained by using 0.50 mg l-1 NAA in vermiculite medium after eight weeks. These results indicate that the P-2 genotype can be micropropagated from the protocol developed for ornamental purposes, clonal testing and tree improvement applications.